Geochemistry of Three Spots on Stream Water around Gedongsongo Hot Springs - Aminin, Agustina L. N.; Suhartana, Suhartana; Sriatun, Sriatun; W., Didik S. (JURNAL SAINS DAN MATEMATIKA, 2013)
Study on the physical characteristics, chemical content of water as well as microbiological composition in the area of ​​geothermal hot springs in Gedongsongo have been done. Water samples were collected on the area within streaming water with moderate temperature. The selection was done on the basis of water that will enter into agricultural and residential areas. Water analysis includes physical analysis, such as temperature, water clarity and odor. While the chemical analysis comprised the oxide content of Mg and Ca. Anion analysis was also performed as sulfate, phosphate, bicarbonate and chloride. The microbiological composition performed using SSCP method for community analysis. The results showed a correlation between the temperature and the content of the anions. The higher temperature of water showed the higher level of anions. The existence of the metal oxide is directly proportional to the levels of the anions. The lower acidity of water showed the higher the levels of hydrogen sulfide. Bacterial composition based on SSCP profile showed a slight different of diversity.